2023
DOI: 10.3389/fcvm.2023.1115135
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic utility of 99mTc-MIBI single photon emission computerized tomography myocardial perfusion imaging in patients with ischemia and non-obstructive coronary artery disease

Abstract: ObjectiveThe aim of our study was to evaluate the prognostic value of gated SPECT MPI in non-obstructed coronary arteries (INOCA) patients, sought to stratify patients more accurately and thus derive more reliable prognostic information.Materials and methodsIn total, 167 patients with INOCA were enrolled. The patients were divided into two groups according to their SSS. Patients were followed-up regularly in terms of major adverse cardiovascular event (MACE), including cardiac death, nonfatal myocardial infarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…The prevalence of this dysfunction typically fluctuates between 26 and 54% [ 20 ]. Recent studies have indicated that left ventricular systolic dyssynchrony and perfusion parameters measured by CZT-SPECT could be used for risk stratification and prognosis prediction of INOCA [ 21 23 ]. Our research findings might complement the clinical decision-making of INOCA patients.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of this dysfunction typically fluctuates between 26 and 54% [ 20 ]. Recent studies have indicated that left ventricular systolic dyssynchrony and perfusion parameters measured by CZT-SPECT could be used for risk stratification and prognosis prediction of INOCA [ 21 23 ]. Our research findings might complement the clinical decision-making of INOCA patients.…”
Section: Discussionmentioning
confidence: 99%